Case study: reconstruction, visualization and quantification of neuronal fiber pathways - Ding, Zhaohua; Gore, John C.; Anderson, Adam W. (Proceedings of the conference on Visualization '01, 2001)
It is of significant interest for neurological studies to determine and visualize neuronal fiber pathways in the human brain. By exploiting the capability of diffusion tensor magnetic resonance imaging to detect local orientations of neuronal fibers, we have developed a system of algorithms to reconstruct, visualize and quantify neuronal fiber pathways in vivo. Illustrative results show that the system is a promising tool for visual analysis of fiber connectivity and quantitative studies of neuronal fibers.